Structural characterization of atypical ACC deaminases from potent PGPR strain H. diazotrophicus E19T - Anirudha Dutta; Abhishek Chatterjee; Surjyatapa Sarkar; Subhendu Bandyopadhyay (The Microbe, 2025)
Hartmannibacter diazotrophicus E19T is well recognized as a plant growth-promoting rhizobacterium (PGPR) able to colonize the rhizosphere of barley and promote its growth under salt stress conditions. An asdS gene, encoding aminocyclopropane-1-carboxylic acid (ACC) deaminase, is crucial and identified in the majority of the sequenced PGPR strains. The ACC deaminase enzyme is a pyridoxal phosphate (PLP)-dependent PALP family protein that stimulates plant growth in stress conditions by reducing level of stress hormone ethylene. Recent genome sequencing of H. diazotrophicus E19T could not identify any acdS or homologous genes, however, the bacteria show in vivo ACC deaminase activity. The H. diazotrophicus E19T encodes three catabolic L-threonine dehydratase TdcB (TdcB1, TdcB2, TdcB3) also belonging to PALP family and may act as atypical ACC deaminase. Amino acid sequence based co-evolution analysis are done to identify active site residues in TdcBs and homology modelling, model validation and structural analysis to identify possible role of the active site residues in catalysis. Co-evolution analysis and homology modelling identified conserved active site residues required for ACC and PLP binding in all three TdcB. Moreover, detailed structural analysis indicates TdcB2 consists of Ser242 that may take part in nucleophilic addition for ACC ring opening, which is crucial step for the ACC deamination reaction. The TdcB1 and TdcB3 may lack ACC deaminase activity as Ser242 in TdcB2 is substituted by Gly235 and Gly240 respectively. Therefore, the present study indicates that TdcB2 may be the atypical ACC deaminase important for PGPR function of H. diazotrophicus E19T.